ECOTHEOLOGY OF THE KAJANG PEOPLE: THE ENCOUNTER BETWEEN ECOLOGY AND THEOLOGY IN THE INDIGENOUS KAJANG COMMUNITY OF SOUTH SULAWESI - M. Yunasri Ridhoh; Andi Alfian (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
The global ecological crisis demands an interdisciplinary approach that goes beyond technical solutions to include spiritual dimensions. This study explores Pasang ri Kajang, the ancestral teachings of the Ammatoa Kajang Indigenous People in South Sulawesi, as a source of ecotheological values integrating ecological awareness with religious belief. Employing a qualitative approach through participatory observation, in-depth interviews, and document analysis, the research was conducted within the Kajang customary territory, focusing on the Ammatoa (customary leader), their teachings, and daily practices. The findings reveal that Pasang ri Kajang functions not only as a customary normative system but also as a contextual theological framework that defines human–nature relations in both ecological and spiritual terms. The principles of simplicity (kamase-masea), prohibitions against environmental exploitation, and rituals of reverence toward sacred forests embody the local praxis of ecotheology. Furthermore, the Ammatoa is identified as an “ecological imam,” a spiritual and ecological leader who interprets Pasang as an “ecological revelation” that safeguards harmony among humans, nature, and the Creator. This study asserts that the local wisdom of Pasang contributes significantly to global ecotheological discourse by offering an alternative narrative to anthropocentric models of development. It demonstrates that faith, culture, and ecology can engage in meaningful dialogue to construct a new, context-sensitive, and spiritually just paradigm of environmental preservation